Predicted changes in the distribution of Antarctic krill in the Cosmonaut Sea under future climate change scenarios - Shiying Lin; Liang Zhao; Jianlong Feng (Ecological Indicators, 2022)
Antarctic krill (Euphausia superba) are the key species of the ecological system in the Cosmonaut Sea. Long-term habitat alterations in krill due to climate change have been considered in recent decades. However, there is still a lack understanding about krill distribution. The MaxEnt model was used to forecast the suitable distribution area of krill for this study, which is based on data from the Coupled Model Intercomparison Project in its sixth phase (CMIP6) in the near future and far future. A total of 145 occurrence points and 15 environmental factors were selected to build the MaxEnt model. The current suitable habitat regions for krill were mostly detected in the western and central regions of the Cosmonaut Sea, which accounted for 10.07% of the total area. The most important environmental variables that influenced krill distribution were minimum surface solar radiation downward (ssrdmin), the mean temperature (tem) and the mean northward velocity (v). In the near future and far future, the suitable area of krill was seen to decline under all shared socioeconomic pathways (SSPs), with the smallest reduction under SSP1-2.6 and the greatest reduction under SSP5-8.5. The suitable area for krill dropped quicker from the near future to the far future than the present to the near future. Krill habitats were expected to shift to the poles. The tem continued to rise in the future under all SSP scenarios, particularly under the high radiative forcing scenario. The increase in water temperature is the main reason for the decrease in suitable areas for Antarctic krill. Our results show the future distribution of krill in the future and provide a reasonable reference for the ecological protection policy of the Cosmonaut Sea.